Relationship between Authentic Leadership and Big Five Personality Trait of Neuroticism: An Empirical Study - Baker, Jasmine J. (Asian Business Review, 2023)
The scope of study that has been done on the significant personality impact of neuroticism on authentic leadership has been relatively minimal. Using a correlational method, this study aims to investigate the relationship between one of the Big Five personality traits, specifically neuroticism, and authentic leadership components (self-awareness, internalized moral perspective, balanced processing, and relational transparency). The authentic leadership questionnaire (ALQ) is used to measure authentic leadership and the Big Five Inventory (BFI) was used to self-report leader personality. The results of this research showed that there is a negative correlation between neuroticism and all authentic leadership dimensions. This was the key takeaway from the study.